2015
DOI: 10.1016/j.cell.2015.08.028
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Sustained Cellulose Synthesis during Salt Stress

Abstract: Abiotic stress, such as salinity, drought, and cold, causes detrimental yield losses for all major plant crop species. Understanding mechanisms that improve plants' ability to produce biomass, which largely is constituted by the plant cell wall, is therefore of upmost importance for agricultural activities. Cellulose is a principal component of the cell wall and is synthesized by microtubule-guided cellulose synthase enzymes at the plasma membrane. Here, we identified two components of the cellulose synthase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
296
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 261 publications
(316 citation statements)
references
References 49 publications
16
296
3
1
Order By: Relevance
“…Upon recovery from osmotic stress, relocalization of CSCs to the plasma membrane was observed in association with microtubuletethered compartments (Gutierrez et al, 2009). Similarly, after prolonged salt treatment, microtubule arrays disappear after 2 h and start to reappear after 8 h, remaining stable thereafter (Endler et al, 2015). This correlates well with the membrane localization dynamics of CSCs (Endler et al, 2015).…”
Section: Changes In the Cell Wall Enable Growth Recoverysupporting
confidence: 61%
“…Upon recovery from osmotic stress, relocalization of CSCs to the plasma membrane was observed in association with microtubuletethered compartments (Gutierrez et al, 2009). Similarly, after prolonged salt treatment, microtubule arrays disappear after 2 h and start to reappear after 8 h, remaining stable thereafter (Endler et al, 2015). This correlates well with the membrane localization dynamics of CSCs (Endler et al, 2015).…”
Section: Changes In the Cell Wall Enable Growth Recoverysupporting
confidence: 61%
“…To assess if any BR-related genes that could potentially influence cellulose biosynthesis were coexpressed with the CESAs, we used the recently developed FamNet (23) with several primary wall cellulose-related genes as queries, including CESA1, CESA6, the CSC-associated KORRIGAN 1 (KOR1) endoglucanase (24,25), the GPI-anchored COBRA (26,27), and the companion of cellulose synthase 1 (CC1) (28). Interestingly, we found that BIN2 was coexpressed with many of the primary wall cellulose-related genes ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Cellulose synthase coaligns with and moves bidirectionally along cortical microtubules (Paredez et al, 2006). A large cellulose synthase interacting protein (CSI1) links microtubule and CESA complexes (Gu et al, 2010), and two companion proteins of cellulose synthase (CC1 and CC2) bind to microtubules and promote microtubule dynamics (Endler et al, 2015).…”
mentioning
confidence: 99%